ADAM11 a novel regulator of Wnt and BMP4 signaling in neural crest and cancer - Pandey, Ankit; Cousin, Hélène; Horr, Brett; Alfandari, Dominique (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Cranial neural crest (CNC) cells are induced at the border of the neural plate by a combination of FGF, Wnt, and BMP4 signaling. CNC then migrate ventrally and invade ventral structures where they contribute to craniofacial development. Methods: We used loss and gain of function experiments to determine phenotypes associated with the perturbation of Adam11 expression in Xenopus Laevis. Mass spectrometry to identify partners of Adam11 and changes in protein expression in CNC lacking Adam11. We used mouse B16 melanoma to test the function of Adam11 in cancer cells, and published database analysis to study the expression of ADAM11 in human tumors. Results: Here we show that a non-proteolytic ADAM, Adam11, originally identified as a putative tumor suppressor binds to proteins of the Wnt and BMP4 signaling pathway. Mechanistic studies concerning these non-proteolytic ADAM lack almost entirely. We show that Adam11 positively regulates BMP4 signaling while negatively regulating β-catenin activity. In vivo, we show that Adam11 influences the timing of neural tube closure and the proliferation and migration of CNC. Using both human tumor data and mouse B16 melanoma cells, we further show that ADAM11 levels similarly correlate with Wnt or BMP4 activation levels. Discussion: We propose that ADAM11 preserves naïve cells by maintaining low Sox3 and Snail/Slug levels through stimulation of BMP4 and repression of Wnt signaling, while loss of ADAM11 results in increased Wnt signaling, increased proliferation and early epithelium to mesenchyme transition.